Biocontrol of the Major Plant Pathogen Ralstonia solanacearum in Irrigation Water and Host Plants by Novel Waterborne Lytic Bacteriophages - Álvarez, Belén; López, María M.; Biosca, Elena G. (Frontiers in Microbiology, 2019)
Three new lytic bacteriophages were found to effectively control the pathogen Ralstonia solanacearum, a quarantine bacterium in many countries, and causative agent of bacterial wilt, one of the most important vascular plant diseases. Bacterial wilt management has been carried out with fluctuating effects, suggesting the need to find alternative treatments. In this work, three lytic phages were isolated from environmental water from geographically distant regions in Spain. They proved to specifically infect a collection of R. solanacearum strains, and some of the closely related pathogenic species Ralstonia pseudosolanacearum, without affecting non-target environmental bacteria, and were able to lyze the pathogen populations within a wide range of conditions comprising environmental values of water temperatures, pH, salinity, and lack of aeration found in storage tanks. The three bacteriophages displayed high efficiency in controlling R. solanacearum, with reductions of the bacterial populations of several orders of magnitude in just a few hours, and proved to be able to survive in freshwater for months at environmental temperatures keeping activity on R. solanacearum, pointing out their suitability for field application through irrigation. Concerning their biocontrol potential, they were effective in reducing high populations of the pathogen in environmental water, and bacterial wilt incidence in planta by watering with either one phage or their combinations in assays with more than 300 plants. This is the first report on effective R. solanacearum biocontrol by applying single or combined bacteriophages through irrigation water in conditions mimicking those of the natural settings. The three phages belong to the Podoviridae family and are members of the T7likevirus genus. They are the first isolated phages from river water with activity against R. solanacearum, showing the longest persistence in natural water reported until now for phages with biocontrol potential, and consistently being able to control the disease in the host plant under environmental conditions. Consequently, the use of these bacteriophages for the prevention and/or biocontrol of the bacterial wilt disease caused by R. solanacearum has been patented. Evidence provided reveals the suitability of these waterborne phages to be effectively considered as a valuable strategy within the frame of sustainable integrated management programs.